Perizinan Modifikasi Bangunan Adat (International Forum of Researchers and Lecturers, 2025)
This study analyzes the legal framework and social implications of the modification licensing process in customary buildings. Modifications are often carried out in response to modernization, material changes, and contemporary functional needs, which have the potential to clash with efforts to preserve cultural values and local wisdom. Using a qualitative approach with case studies in several indigenous villages in Indonesia, data was collected through in-depth interviews, observations, and review of licensing documents and related policies. The results of the study show that there is a tension between formal licensing laws (such as Building Permits/IMB) and customary laws that apply in local communities. An effective licensing process requires intensive dialogue and collaboration between local government authorities, customary institutions, and building owners to ensure modifications still respect the values contained in cultural heritage. The study recommends a flexible and consultation-based licensing framework that harmoniously integrates positive legal aspects and customary norms, while promoting community awareness and participation in heritage conservation.